Financial Statement Analysis / Using Financial Accounting Information: Fourth Edition - Gibson Charles H (Pws-Kent Publishing Company, 1989)
Fundamental Covepts, Introduction to Financial Statements - Balance Sheet, Introduction to Financial Statements - Income Statement and Statement of Retained Earnings, Basics of Analysis, An Illustration of Statement Analysis: Cooper Tire and Rubber Company, Liquidity of Short-Term Assets and the Related Short-Term Debt-Paying Ability, Long-Term Debt-Paying Ability, Analysis of Profitability, Analysis of the Investor, Statement of Cash Flows, An Illustration of Statement Analysis: Cooper Tire and Rubber Company, Analyzing the Impact of Inflation on Financial Statements, Expanded Utility of Financial Ratios, Statement Analysis for Special Industries: Banks and Utilities and Oil and Gas and Transportation, Personal Financial Statements and Accounting for Governments and Other Non Profit Institutions, Comprehensive Case - Worthington Industries, Bibliography, Index.